Mosaic Panel on Refrigerium from Sinop Balatlar Church and its Place in Byzantine Iconography - Ozan Hetto; Gülgün Köroğlu; Nilay Çorağan (Art-Sanat)
Balatlar Church, whose identity and usage phases can be determined with the excavations that started in 2010, is the only structure in Sinop city history whose purpose of the use is known. The mosaic finds unearthed in the frigidarium space of the building, which is known in the literature as the Balatlar Church and whose first establishment is understoodto be the Roman Imperial Bath, is a unique material that differs in style and iconography from the mosaics unearthed in Sinop and its surroundings. Mosaics made in the opus tesselatum technique, which can be dated to the end of the 4th century and the beginning of the 5th century, as a result of the data and stylistic analyzes obtained in the studies, have an important position in Byzantine art and Christian iconography with their unique composition schemes. One of the most striking examples of these mosaic finds unearthed during the Balatlar Church Excavation is the mosaic panels numbered 3 and 6, which contain scenes on the “refrigerium”. As it is known, refrigerium, which means relief, is a scene that has been frequently depicted in Byzantine art for many years as a preview of paradise. Especially in the Early Byzantine period, different types of refrigerium scenes, which were spread over a wide geography, were depicted on works of art made of different materials. In the study, the examples of the Balatlar Church will be evaluated and the place and importance of the refrigerium, which is one of the most frequently encountered themed scenes in Byzantine art, will be determined.